Naumenko N. V. Еlements of artistic synthesis in Volodymyr Zatulyviter’s works - Naumenko N. V. (Philological Treatises, 2020)
The article gives an analysis of several poetic images – components of verse works by V. Zatulyviter, connected with artistic synthesis. There was shown that the key purpose accomplished by the author is to “poetize” the creative work of a versifier, an actor, a musician, a sculptor, an architect etc. Thanks to this, the notion of creativity has concentrated the diverse associations that vary depending on the author’s or the recipient’s esthetic experience.